Alternatif Penyelesaian Sengketa Ketenagakerjaan Melalui Mekanisme Arbitrase di lndohesia - mila karmila adi (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The Indonesian Labour Dispute Resolution Law: No.22, 1957,-has provided two kinds of mechanism, namely compulsoly arbtration and voluntary arbitration. Both of them are non-litigation dispute resolutions, but, in tact, the voluntary arbitration is rarely used by the partiesto settle their labour dispute. The voluntary arbitration (arbitration) givesless steps on its mechanism and it-has more benefits for the parties, especially on its confidental process. The arbitration-process will fit as the altemative labour dispute resolution, in-Indonesia in the Globalization Era.